1999
DOI: 10.1002/etc.5620181217
|View full text |Cite
|
Sign up to set email alerts
|

Membrane toxicity of linear alcohol ethoxylates

Abstract: Abstract-The membrane toxicity of linear alcohol ethoxylates (AEO/single reference compounds and technical mixtures) was investigated with an in vitro method based on time-resolved spectroscopy on energy-transducing membranes. The nonspecific membrane perturbation of narcotic chemicals can be quantified by the degree of disturbance of buildup and relaxation of the membrane potential in membrane preparations of the purple bacterium Rhodobacter sphaeroides. The effect concentrations obtained for this narcotic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…The cell membranes of AOB do not seem to be fundamentally different from those of many other gram-negative bacteria; the lipid composition is quite similar (55,62), and even if AOB have a larger specific membrane area than most other bacteria (51), it is difficult to see how this could contribute to their greater sensitivity to LAS. However, monomers of LAS and other surfactants are known to increase the permeability of biological membranes (13,14,43,64), and this could lead to uncoupling reactions during energy metabolism. Due to the low energy yield from NH 4 ϩ oxidation (8,34) and the high energy requirement for CO 2 fixation (34,35), it is likely that AOB are particularly sensitive to such uncoupling surfactants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell membranes of AOB do not seem to be fundamentally different from those of many other gram-negative bacteria; the lipid composition is quite similar (55,62), and even if AOB have a larger specific membrane area than most other bacteria (51), it is difficult to see how this could contribute to their greater sensitivity to LAS. However, monomers of LAS and other surfactants are known to increase the permeability of biological membranes (13,14,43,64), and this could lead to uncoupling reactions during energy metabolism. Due to the low energy yield from NH 4 ϩ oxidation (8,34) and the high energy requirement for CO 2 fixation (34,35), it is likely that AOB are particularly sensitive to such uncoupling surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the difficulties involved in cultivation of AOB, there is still a general lack of data concerning the effects of toxic chemicals on the general physiology of these bacteria. Previous studies have dealt mostly with specific nitrification inhibitors targeting the NH 4 ϩ monooxygenase enzyme (5, 42), and very little is known about other targets of toxicants in AOB cells.Xenobiotic surfactants comprise a very important group of potentially toxic compounds that are believed to be harmful due to disruption of the function and structure of bacterial membranes (11,13,14,43,64). The linear alkylbenzene sulfonates (LAS) constitute the quantitatively most important group of synthetic surfactants used today, and the use of these compounds will likely increase in the years to come (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chem. 28, 2009 1381 their rapid growth rate is useful for studying toxicity effects over several generations in a short time period [20,21]. Our results revealed that NaN 3 enhanced the toxicity of the metabolites TCHQ and TCC.…”
Section: Introductionmentioning
confidence: 91%
“…Although the mode of action of surfactants against insects remains unknown, the interaction with biological membranes is believed to be an explanation [26,27]. Nonionic surfactants can also interfere with enzyme activity by binding with proteins.…”
Section: Discussionmentioning
confidence: 99%